2016
DOI: 10.1016/j.ecresq.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Child care enrollment decisions among dual language learner families: The role of Spanish language instruction in the child care setting

Abstract: Data from the Head Start Impact Study (N = 1,141) and the Head Start Family and Child Experiences Survey, 2009 Cohort (N = 825) were used to describe child care enrollment decisions among Spanish-speaking Dual Language Learner (DLL) families. In particular, logistic regression models tested which child, family, and institutional characteristics predicted enrollment in early care and education (ECE) settings that used Spanish for instruction versus enrollment in settings that did not use Spanish. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The maintenance of a multicultural and multilingual school setting is attractive to parents. In previous studies, parents have been shown to tend to enroll their children in centers where providers speak their children’s HL, preferring a school that is culturally close to their own [ 59 , 71 ]. Promoting a bilingual environment at Head Start centers also increases families’ involvement in school, leading to stronger relationships between students and teachers, and promoting improved academic competency and attitudes in children [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of a multicultural and multilingual school setting is attractive to parents. In previous studies, parents have been shown to tend to enroll their children in centers where providers speak their children’s HL, preferring a school that is culturally close to their own [ 59 , 71 ]. Promoting a bilingual environment at Head Start centers also increases families’ involvement in school, leading to stronger relationships between students and teachers, and promoting improved academic competency and attitudes in children [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…To use ECE options available in their community, parents need clear and accurate information that can support their search process and enrollment decisions. Several barriers may constrain ECE information for low-income Latinx families, including limited English proficiency (Miller 2016), restricted social networks and information flows that favor personal connections (e.g., friends, neighbors, relatives, coworkers) (Chaudry et al 2011), and fear to engage with public programs because of immigration-related concerns and discrimination (Vesely et al 2015). Limited program outreach to Latinx communities and insufficient translation/interpretation services, along with administrative burden during the application or enrollment process (e.g., in-person office visits, documentation requirements), further limit families' access to ECE, especially when compounded with other barriers (Greenberg, Adams, and Michie 2016).…”
Section: Hispanic Access To Ece That Can Be Engaged In With Reasonable Effortmentioning
confidence: 99%
“…There is also emerging qualitative evidence that low-income immigrant mothers may prioritize care that meets their scheduling needs – that is, evening or overnight care – if they are working non-traditional hours due to documentation or language barriers (Vesely, 2013). Recent research on Spanish-speaking dual-language learners (DLLs), many of whom are immigrants, has shown that children whose first language is Spanish are more likely to be enrolled in in an ECE arrangement that uses Spanish for instruction as opposed to another language (Miller, 2016), suggesting that Spanish-speaking immigrants may prefer ECE with Spanish-speaking caregivers over English-speaking caregivers. Low-income immigrant parents may struggle with conflicting preferences for ECE that is affordable and available during non-standard work hours (as do many low-income workers), versus a setting that promotes acculturation and academic preparation, versus one that features a caregiver who speaks the native language and provides cultural continuity, for example.…”
Section: Previous Researchmentioning
confidence: 99%